Sistem Informasi Jadwal Siaran Studio 5 Universitas Muhammadiyah Banjarmasin - Ansari, Rudy; Alkaff, Muhammad (Jurnal Teknologi Berkelanjutan, 2023)
Studio 5 Muhammadiyah University Banjarmasin, there are 2 (two) employees, the scheduling process at studio 5 is carried out by sending a letter to the resource person concerned. Scheduling is also done by taking notes on the whiteboard in the studio5. Then when the filming process, video editing has been carried out, then the video has been uploaded to the YouTube channel, the notes on the whiteboard are deleted or cleaned. The aim of making this schedule is so that all schedules are recorded well and can be displayed visually. In this system, an application is created that can be displayed on the television screen at the Muhammadiyah University of Banjarmasin, where before this application was created, it was still written on a blackboard for the schedule and implementation of events. This information system was created based on the Software Development Life Cycle (SDLC) method, where the stages of the method include system analysis by directly conducting interviews with related parties, system design using Unified Modeling Language (UML) design for the diagram stages, namely Usecase Diagram, Sequence Diagram, Activity Diagram, then for the database using MySql Workbench, implementation, testing and maintenance for implementation using Laravel tools. So that with these stages it is possible to clearly build an information system for broadcast schedules for Studio 5 of Muhammadiyah University, Banjarmasin. The Studio 5 broadcast schedule information system has several features, starting from the broadcast proposal feature from users and the broadcast proposal feature from admin, the master data feature which includes section data, editor data, cameraman data, and moderator data which can be managed by the admin, a validation feature where broadcast suggestions from users can be scheduled because they have been validated by the admin, and a print or report feature where in this feature the data contained in the broadcast data is printed in excel format.